DEVELOPMENT OF COMPUTER-BASED TESTS USING MOODLE LMS ON THE MATERIAL OF SOCIAL CONFLICT AND INTEGRATION - Omika, Hefri Asra; Marzal, Jefri; Idrus, Ali (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Along with the development of information and communication technology, the implementation of computer-based tests has become an important requirement in the learning process. Moodle LMS is a platform that provides a quiz feature that can be used as a computer-based test medium. This study aims to analyze the quality and feasibility of computer-based questions on conflict and social integration using the Moodle LMS. This research is adevelopment research with a 4-D model. The research subjects were 64 students of class XI IPS at SMAN Titian Teras H. Abdurrahman Sayeoti. The instruments used were validation sheets for assessing the quality of the questions, the appropriateness of the media, student response questionnaires, and the quality of the items. Based on the results of the question feasibility test by material experts and media experts with an average score of 83% (Very Good). The results of the item analysis obtained valid questions of 80% with a reliability of 0.890. The difficulty level of the questions in the easy, medium, and difficult categories were 48%, 46%, and 6%, respectively. Different power of questions with a good category of 40%, sufficient category of 50% and 10% bad. Based on the description above, it can be concluded that computer-based questions on conflict and social integration have good quality questions and are very appropriate to be used as sociology learning outcomes tests.